PENERAPAN METODE FINITE STATE MACHINE PADA NON PLAYER CHARACTER(NPC) GAME ACTION STRATEGY “OUROBOROS” - Safitra, Wahyu; Faisol, Ahmad; Adi Wibowo, Suryo (Institut Teknologi Nasional Malang, 2020)
Game with strategy genre is a type of game that is quite popular among children and adults. The strategy game itself has various indirect benefits that will be experienced by the players, where players must think and analyze what steps or actions must be taken before taking action. As one of the key characters for building challenges in the game, the Finite State Machine method will be applied to NPCs and objects that will trigger traps. By using the FSM method, each state can apply a variety of algorithms that allow NPCs to perform various actions when there is an interaction with a player. The results of this study are in the form of a game application that can be run on the windows desktop platform and it can be concluded that almost all functions both on objects, main functions, and enemies can run well, and 86% of 10 respondents gave good responses. Thus the use of the finite state machine method is suitable to be applied to NPC games with the action strategy genre.